Inovasi Kemasan Produk dan Pelabelan Untuk Menciptakan Nilai Tambah pada Produk UMKM Dapur Keysha di Desa Mranggonlawang - Alfi Rizka; Yuniningsih Yuniningsih (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
MSMEs are seen as a driving force in domestic economic development. However, there are still some problems encountered, namely marketing strategies that are less than optimal and unattractive. Keysha's kitchen is one of them. After observing, the packaging still looks ancient and does not have a label. Thus, it is necessary to provide assistance regarding packaging innovation from Dapur Keysha according to the aesthetic standards of current trends and their uses. The purpose of this activity is to provide knowledge and understanding to MSME actors regarding the urgency of product packaging and increase the added value of the products produced. There are three methods used, namely observation, socialization, and mentoring. At the end of this activity, modern packaging and labeling were obtained. The latest packaging is modified from a standing pouch to a jar packaging which can be made as hampers. Then there is the making of labels that include product types, brands, expiration dates, MSME social media, and other information.